Significance of coconut as an ingredient in Koli Cuisine - Mumbai Archive Project Team (Jio Institute, 2024)
Much of Koli cuisine includes grated coconut as an ingredient or garnish. It improves the flavour and texture of chutneys and curries. A common element in many Koli meals, particularly stews and curries, is coconut milk.